Human Uterine Transplantation: A Review of Outcomes From the First 45 Cases. Issue 3 (September 2020) - Jones, B.P.; Saso, S.; Bracewell-Milnes, T.; Thum, M.Y.; Nicopoullos, J.; Diaz-Garcia, C.; Friend, P.; Ghaem-Maghami, S.; Testa, G.; Johannesson, L.; Quiroga, I.; Yazbek, J.; et al.
Abstract : ( BJOG . 2019;126:1310–1319) Women with absolute uterine factor infertility (AUFI) cannot conceive or sustain pregnancy due to a dysfunctional uterus or absence of a uterus. Because adoption and surrogacy both have many limitations, researchers have developed uterine transplantation (UTx) as a potential solution for women with AUFI to conceive and deliver a genetically related child. After the first live birth following UTx occurred in 2014, obstetric researchers have published studies and collected detailed information on 45 different transplant cases, including 9 live births. This review compiles the data and outcomes from these 45 cases to note trends and make recommendations for best care practices.